2015
DOI: 10.17140/aftnsoj-1-123
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of Polyunsaturated Fatty Acids and its Impact on Food Quality and Human Health

Abstract: CitationTao L. Oxidation of polyunsaturated fatty acids and its impact on food quality and human health. Mini ReviewPage 135 ABSTRACTFor many years, both preclinical and clinical studies have provided evidences to support the beneficial effects of ω-3 Polyunsaturated fatty acids (PUFAs), particularly Eicosapentaenoic acid (EPA) and Docosahexaenoic acid (DHA) in the prevention of chronic diseases. However, recently, an increasing number of studies reported adverse or contradictory effects of ω-3 PUFAs on huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
51
0
9

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(61 citation statements)
references
References 49 publications
1
51
0
9
Order By: Relevance
“…Free oxygen in the air will oxidize the double bonds of unsaturated fatty acids in food, and oxidation of fatty acids followed by the formation of hydrogen peroxide (H2O2) which causes rancidity. Tao (2015) states that oxidation of fat begins with hydrolysis of triglycerides to produce fatty acids and glycerol. Furthermore, unsaturated fatty acids are oxidized to produce hydroperoxide, then aldehydes, ketones, and the peak is the formation of malonaldehyde.…”
Section: Peroxide Valuementioning
confidence: 99%
“…Free oxygen in the air will oxidize the double bonds of unsaturated fatty acids in food, and oxidation of fatty acids followed by the formation of hydrogen peroxide (H2O2) which causes rancidity. Tao (2015) states that oxidation of fat begins with hydrolysis of triglycerides to produce fatty acids and glycerol. Furthermore, unsaturated fatty acids are oxidized to produce hydroperoxide, then aldehydes, ketones, and the peak is the formation of malonaldehyde.…”
Section: Peroxide Valuementioning
confidence: 99%
“…Oksidasi lemak diawali dengan hidrolisis trigliserida menghasilkan asam lemak dan gliserol. Selanjutnya asam lemak tidak jenuh teroksidasi menghasilkan hidroperoksida, kemudian aldehid, keton dan puncaknya adalah terbentuknya malonaldehid (Tao, 2015). Oksidasi dapat dipicu adanya panas, sinar, logam dan oksigen menghasilkan ROS (Reactive Oxygen Spesies) seperti aldehid, peroksida, kolesterol oksida.…”
Section: Aktivitas Antioksidasi Bakso Dengan Penambahan Gel Lidah Buayaunclassified
“…Lidah buaya atau aloe vera diketahui mengandung senyawa flavonoid yaitu quercetin, mericetin dan kaempferol yang dapat menangkap radikal bebas (Sultana & Anwar, 2008). Hasil oksidasi asam lemak berupa radikal bebas berbentuk reactive oxygen spesies (ROS) (Tao, 2015) seperti radikal alkoxi dan radikal peroksida (Cheng, 2016). Aktivitas antioksidasi daun lidah buaya cukup tinggi walaupun telah diekstrak dan atau diolah menjadi bubuk instan (Wariyah & Riyanto, 2016), namun dalam bentuk gel segar aktivitas antioksidasinya paling tinggi.…”
unclassified
“…PUFAs are known to have antibacterial activity against a wide range of bacteria [10][11][12], which is an important characteristic needed in the food industry to prevent foodborne or food spoilage bacteria growth. However, recent study reported that PUFAs have high susceptibility to lipid oxidation, which limits the practical uses of this compound [13].…”
Section: Introductionmentioning
confidence: 99%